Replacement model for robots in automotive assembly plant - Majid, M.A.A. (Asian Research Publishing Network, 2016)
The robots operated in automotive assembly plant are a large portion of investment which contributed to the automation level of the manufacturing assembly line. Significant impact on the profit and lost (P&L) of the company contributed from the operating efficiency of equipment including robots, in term of maintaining cost and replacement cost. Timely replacement could reduce the downtime which might result in significant saving on the company P&L. The objective of this research is to develop a replacement model for replacement of robots in automotive assembly line. The approaches used in this research are 1) gathering mean time between failures (MTBF) and mean time to repair (MTTR) data for availability assessment, 2) computational of the defender marginal cost (MC) and challenger equivalent uniform annual cost (EUAC) and 3) using spreadsheet computational model for sensitivity analysis. From the analysis the robot with lowest availability (99.41) had the lowest MTBF of 5280 hours. The robot was taken as a candidate for replacement. Replacement study using MC and EUAC analysis was done for the robot and the potential candidate for replacement. Upon computing the defender MC and challenger EUAC cost analysis, the minimum EUAC of Malaysian Ringgit 68,619 and MC of Malaysian Ringgit 62,000, if it is kept in the services for only five (5) years. The MC of defender in year 5 is Malaysian Ringgit 71,000, hence it is due for replacement. Based on the sensitivity analysis, the initial capital investment is the most sensitive factor compared to other factor. The current robot can be maintained for one more year in service. Â© 2006-2016 Asian Research Publishing Network (ARPN).